Evaluation of Efficacy and Safety of Transdermal Electrical Stimulation in Treatment of Knee Osteoarthritis - Kaiming LI; Shangquan WANG; Linghui LI; Qing ZHANG; Long LIANG; Ming CHEN; Jiawen ZHAN; Jing YIN; Zhuo WANG (康复学报)
Objective:To systematically evaluate the efficacy and safety of transdermal electrical stimulation (TES) in the treatment of knee osteoarthritis (KOA).Methods:A computerized systematic search of randomized controlled trials published in CNKI, Wanfang, VIP, Embase, PubMed, CBM, Cochrane libraries on the treatment of KOA by TES prior to October 2019. Literature data were extracted and reviewed independently by two reviewers, quality evaluation was conducted following the Cochrane collaborative standards, and Meta-analysis was performed using RevMan 5.3 software.Results:According to the inclusion criteria, 6 randomized controlled trials with a total of 991 patients were included, including 502 in the experimental group and 489 in the control group, with a ratio of 1∶1. Meta-analysis results showed that the overall effective rate[RR=0.08, 95%CI(0.01, 0.61), P=0.02], visual analogue pain (VAS) score[MD=1.47, 95%CI(1.16, 1.77), P< 0.001]and incidence of adverse reactions[RR=0.08, 95%CI(0.01, 0.61), P=0.02]in the experimental group were significantly better than those in the control group. Lysholm knee function evaluation function score scale[MD=3.71, 95%CI(-1.59, 9.01), P=0.17]showed no significant difference between the two groups.Conclusion:Transdermal electrical stimulation has significant advantages in the treatment of KOA, which can effectively reduce joint pain, improve joint function and quality of life.